PENERAPAN PIDANA PEMECATAN TERHADAP ANGGOTA TENTARA NASIONAL INDONESIA SEBAGAI PELAKU TINDAK PIDANA - Mr. Supriyadi (Fakultas Hukum Universitas Gadjah Mada, 2008)
The judge basic consideration in condemning discharge sentence can be seen from the crime which is committed by military and its effect to the name of Indonesian National Armed Forces (TNI). When the crime which is committed by military gives negative effect to the norm of TNI, so it can be used as a basic consideration to give discharge sentence. Besides, it can be seen from the status of the military who committed a crime. When the military did a crime repeatedly, it can be used as a basic to give a discharge sentence. The existence of discharge sentence still need to be taken care in the future to give deterrent effect to the military. The regulation of discharge sentence in KUHPM must be separated with Civil Penal Code (KUHP) in separated codification. In the future, KUHPM has to formulize explicitly about criteria in discharge sentence application to military as an offender.